2020
DOI: 10.1002/uog.21971
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic characteristics of post‐molar gestational trophoblastic neoplasia at diagnosis and during follow‐up, and relationship with methotrexate resistance

Abstract: Objectives To describe the sonographic characteristics of post‐molar gestational trophoblastic neoplasia (GTN) at diagnosis and during follow‐up, and to assess their association with methotrexate (MTX) resistance (R) as first‐line chemotherapy. Methods This was a retrospective study of all women treated for post‐molar GTN at Karolinska University Hospital, Stockholm, Sweden, between October 2010 and December 2017, who had undergone expert transvaginal ultrasound assessment ≤ 2 weeks prior to, or ≤ 1 week after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
3
7
0
Order By: Relevance
“…Furthermore, UtA-TAmean was identified on multivariate logistic regression analysis as a significant independent predictor of MTX resistance. Therefore, our results are not only consistent with previous research [23][24][25][26] , but also demonstrate new Doppler predictors for MTX resistance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, UtA-TAmean was identified on multivariate logistic regression analysis as a significant independent predictor of MTX resistance. Therefore, our results are not only consistent with previous research [23][24][25][26] , but also demonstrate new Doppler predictors for MTX resistance.…”
Section: Discussionsupporting
confidence: 93%
“…These two distinct groups (with and without myometrial invasion) of patients with low-risk GTN had been shown to have very different uterine vascularization characteristics. Several ultrasound parameters have been reported to predict MTX resistance in patients with low-risk GTN, such as a sizeable myometrial invasion (≥ 4 cm diameter) 26 , a low TCV-RI (≤ 0.28) 25 and a low UtA-PI (≤ 1.0 or 1.1) 23,24 . In this study, we analyzed 17 ultrasound features using univariate logistic regression analysis and identified 12 significant predictors of MTX resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malek [26]. They did not mention indices or cut off values for prediction of GTN by Doppler and depended in the sonographic morphological assessment on size of lesion, which is usually a late sign for diagnosis, Doppler of tiny vessels of the sub endomtrium and myometrium used in the current study is an earlier predictor for the disease.…”
Section: Discussionmentioning
confidence: 87%
“…Transvaginal ultrasound (US) has acquired a substantial role in diagnosing and managing GTNs with the development of Doppler techniques. [7][8][9] GTNs and other benign pregnancy-related uterine diseases can sometimes appear similar on greyscale and colour Doppler US, manifesting as focal lesions with rich blood flow signals. 10 Hence, it is crucial to develop new imaging methods as a complement to conventional US for diagnosing GTNs.…”
Section: Introductionmentioning
confidence: 99%